2017
DOI: 10.1080/1343943x.2017.1418629
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of late-season rice in South China

Abstract: a Southern regional collaborative innovation center for Grain and oil crops (cicGo), Hunan agricultural university, changsha, P.r. china; b Key laboratory of crop cultivation and Farming System, Guangxi university, nanning, P.r. china ABSTRACT Improving rice yields is critical for global food security. China is a major rice-producing country having two rice cropping systems, i.e. single-season rice cropping system and a double-season system with both early-and late-season rice. There have been reports on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…() evaluated a series of inbred japonica varieties and determined that the grain yield of inbred japonica varieties was 10.00 ± 0.21 t ha −1 , which did not differ significantly from the indica varieties (9.40 ± 0.96 t ha −1 ). Furthermore, in the current study, the Nanjing46 variety had a grain yield of 7.3 t ha −1 during the 2016 late season, which was comparable to the grain yield of the elite indica rice in the late season (Huang et al., ). These results indicated a remarkable variability in grain yield in the inbred japonica varieties, and there are great potential to breed out the high yield inbred japonica for the late season.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…() evaluated a series of inbred japonica varieties and determined that the grain yield of inbred japonica varieties was 10.00 ± 0.21 t ha −1 , which did not differ significantly from the indica varieties (9.40 ± 0.96 t ha −1 ). Furthermore, in the current study, the Nanjing46 variety had a grain yield of 7.3 t ha −1 during the 2016 late season, which was comparable to the grain yield of the elite indica rice in the late season (Huang et al., ). These results indicated a remarkable variability in grain yield in the inbred japonica varieties, and there are great potential to breed out the high yield inbred japonica for the late season.…”
Section: Discussionsupporting
confidence: 67%
“…However, there were large yield differences in late‐season rice within rice types. Previous research has indicated that grain yields is ranked in the order of indica‐japonica hybrid variety > elite indica variety > inbred japonica variety (Cheng et al., ; Huang et al., ). The superiority of the indica‐japonica hybrid variety over the inbred japonica variety was confirmed in the current research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GNP and EPN had super-parental advantages (Li et al, 2016). The highest yield of lateseason hybrid rice was 9.64 t ha -1 , whibch produced a 6-26% higher grain yield than that of the other cultivars because the higher grain yield was driven by improvements in sink-source capacity (biomass production, panicles and spikelets per m −2 , and grain weight) (Huang et al, 2017b); In this study, it was shown that the average yield of late-season rice was 8.44 t ha -1 and 8.75 t ha -1 in 2017 and 2018, respectively (Table S3). Compared with the inbred lines, the average yield of late-season hybrid rice increased by 4.65% and 12.35% in 2017 and 2018, respectively (Table S4).…”
Section: Discussionmentioning
confidence: 99%